Gene-environment interactions in freshwater prawns Macrobrachium rosenbergii / Tahereh Alinejad - Tahereh , Alinejad (2019)
Temperature is an essential factor in establishing growth, reproduction and distribution of organisms. In the current fluctuating climate circumstances, especially one as humid as Malaysia’s aquatic organisms’ survival is dependent on their adaptability to their environment’s thermal changes. These adaptive characteristics can be either physiological or genetic. Temperature also plays an important role in the innate immune response to prawns and could alter the functional expression of immune genes. This study investigated the impact of temperature, as n contributor to environmental stress on immune gene expression in freshwater prawn, Macrobrachium rosenbergii, and on the histological and physiological changes of three organs, hepatopancreas, hemolymph and muscle. The expression of 14 genes (AK1, Lec1, Lec2, Lec3, Lec4, Ta-Lec, Ppo, PpoAIII, Hmo, HSP70, Chp, ALF2, NfkBI-α2, LAPs 2), representing five different pathways (metabolite, prophenoloxiade (PPO), lectin, apoptosis and chaperon) was studied at four different temperatures, 24 °C, 28 °C, 32 °C, 36 °C, at 6 hours and 12 hours post thermal stress, in these organs. The weight, body colour, hemocyte colour, count and viability. Hepatopancreas Somatic Index (HIS), phenoloxidase activity, total protein quantification of each prawn was observed at each time point. The experiments were carried out under three conditions: controlled laboratory conditions, good farm management and poor farm management. The gene expression pattern observed was similar in all three conditions. Higher gene expressions were observed at elevated temperatures (32 °C and 36 °C) in hemolymph at both timepoints. The chaperon (HSP70, Chp, Hmo) and PPO (Ppo, PpoAIII) genes showed a higher expression than the metabolite (AK1, ALF2), apoptosis (NfkBI- α2, IAPs 2) and lectin (Lec1, Lec2, Lec3, Lec4, Ta-Lec) genes. In contrast. Lower expressions were observed at 24 °C and 36 °C in muscle and hepatopancreas. The chaperon, PPO and lectin genes showed higher expression levels in comparison with the metabolite and lectin genes at both six- and twelve-hours post-stress in muscle and hepatopancreas. At higher temperatures, discoloration of hemocyte, reduction in hemocyte count, reduction in hemocyte viability, decrease in total protein, reduction in weight, reduction in HIS, reduction in PPO activity and body discoloration were observed. Histological examinations revealed formation of abnormal lumen in hepatopancreas, together with tubule rupture, muscle necrosis and degeneration, at elevated temperatures. The histological and physiological changes observed, in comparison with the gene expression observed, suggest that the freshwater prawn can adapt genetically in order to attempt to survive under different thermal conditions, however, this is impossible physiologically.